“Portrayal of Essential Indian Life and Culture in R.K.Narayan” - Jayaceelan, Rev.R.J.E. (Ph.D. in English Literature, 2002)
Each Indian writer has portrayed Indian life and culture according to the inner essence impressed upon his heart and mind and Narayan in his novela, fifteen in number, was no exception to this fact. British colonial education and its colonial policies, which engendered a new class, the Indian middle class, was the focus of his stories. His fictional habitat, Malgudi was the space in which the middle class men and women matured. Striving towards the four ends of Indian life truth, wealth, happiness, and final liberation. The women in the novels are essential formulators of the four ends and contribute to the new Indian essence Since these four traditional ends are defined by the traditional religious of India, religion plays an important role in the life of Malgudi. Life’s scenes enacted within these traditional goals is compromised and amalgamated with a new western form, the novel, and give rise to the dilemma of the Indian new class, provoking laughter and tears, giving rise to a new type of Indian comedy, traditional yet modern. In all this it is the new language, the unique voice of the Indian storyteller in the author, which helps to design the new Indian essence of life and culture that Narayan’s fifteen novels help to portray.